Infertile Women's Perception on the National Support Program for Infertile Couples - Soo Kyoung Hann; Hee Sun Kang (Korean Society of Women Health Nursing, 2015)
PURPOSE: The purpose of this study was to explore the perception of infertile women on the use of the national support program that provides medical expense aid to infertile couples. METHODS: Thirty Korean infertile women participated in five focus groups. Data were collected from January to August 2014. After obtaining permission from the participants, each session of the focus group was audio-taped and transcribed. The responses were analyzed using qualitative content analysis. RESULTS: The main themes identified from the sessions with the participants were "feeling thankful for the reliable support program," "feeling happy or unhappy," "enduring inconveniences," and "hoping for a more comprehensive support service." Although most of the participants perceived the benefits of the national support service positively, they stated that the service was not comprehensive because it did not cover all the medical expenses for tests and other medical treatments. CONCLUSION: The benefits given to infertile couples by the program should be increased by covering all the medical expenses, expanding its criteria to include more eligible candidates, and by including special leave benefits for working women. Furthermore, it is essential to take measures for infertility prevention at the individual and national policy levels.